Nutrient Release Pattern of Decomposited Leaf Litter in Different Multipurpose Trees - Bhalawe, Shailendra; Kukadia, M. U.; Nayak, Dileswar (Indian Forester, 2013)
The investigation undertaken to find out the rate of decomposition of leaf litter of seven multi-purpose tree species, viz., Tectona grandis, Eucalyptus tereticornis, Dendrocalamus strictus, Terminalia bellirica, Cassia fistula, Casuarina equisetifolia and Terminalia arjuna for 195 days i.e. from first fortnight of July 2009 to second fortnight of January 2010. The litter bag of nylon net (1mm mesh size), 20x20 cm. in size, containing 10g air-dried samples were incubated on surface in the first week of July 2009. Litter bags of each species were placed on the plantation field of respective species. For each species 3 litter bags were recovered at fortnight intervals for the study of weight loss in dry matter due to decomposition. Fresh leaf litter were also chemically analysed for N, P, and K using standard prescribed procedure. Significantly the highest amount of nitrogen release (%) was recorded in Eucalyptus tereticornis which was followed by Dendrocalamus strictus. Among different multipurpose tree species the maximum amount of phosphorus release was recorded in Cassia fistula and maximum amount of potassium release percentage was in Eucalyptus tereticornis which was at par with Terminalia bellirica.